2015
DOI: 10.3389/fpsyg.2015.00939
|View full text |Cite
|
Sign up to set email alerts
|

Toward an ecological analysis of Bayesian inferences: how task characteristics influence responses

Abstract: In research on Bayesian inferences, the specific tasks, with their narratives and characteristics, are typically seen as exchangeable vehicles that merely transport the structure of the problem to research participants. In the present paper, we explore whether, and possibly how, task characteristics that are usually ignored influence participants’ responses in these tasks. We focus on both quantitative dimensions of the tasks, such as their base rates, hit rates, and false-alarm rates, as well as qualitative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…In short, Bayesian reasoning is generally a challenging task, which depends on a full understanding of the situation and clear thinking about the dynamics of the situation. Consistent with the thesis that different mental models might influence reasoning and decision making, Hafenbrädl and Hoffrage (2015) found that the contexts used in different Bayesian reasoning tasks (e.g., whether the cover story was about medical diagnosis, or predicting colored balls in an urn, or about college admission exams) actually could influence the responses of participants. Specifically, there were differences due to factors such as whether the task involved a norm violation or not and whether the stakes involved were high or low.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…In short, Bayesian reasoning is generally a challenging task, which depends on a full understanding of the situation and clear thinking about the dynamics of the situation. Consistent with the thesis that different mental models might influence reasoning and decision making, Hafenbrädl and Hoffrage (2015) found that the contexts used in different Bayesian reasoning tasks (e.g., whether the cover story was about medical diagnosis, or predicting colored balls in an urn, or about college admission exams) actually could influence the responses of participants. Specifically, there were differences due to factors such as whether the task involved a norm violation or not and whether the stakes involved were high or low.…”
Section: Introductionsupporting
confidence: 66%
“…Would they even cause significant behavioral deviation if their cognitive counterparts could be detected? One may alternatively argue that the stakes differ by context (e.g., catching a cold vs. physical assault), and that this can influence Bayesian reasoning (Hafenbrädl and Hoffrage, 2015), so therefore these influences must be controlled for in order to evaluate any effects of the contexts a mental model metaphors. The difficulty with this argument is that it is essentially about the partialing of effects as due to different factors, but these factors have not been identified in any principled way (e.g., other than post hoc ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we changed the frequency data in the two problems, we explicitly asked participants to imagine two different scenarios for the same fictional city. Previous research shows that changing the numerical values of the problem does not affect reasoning strategies, and we thus made the assumption it would not affect our analysis (Hafenbrdl and Hoffrage 2015). The presentation of the scenarios was counterbalanced between participants to reduce carryover effects.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…While this may be taken as evidence that Bayesian reasoning with percentage information is independent of the number of events referred to, this does not necessarily imply that single-event probabilities are as easily understood as relative frequencies expressed as percentages (e.g., Brase, 2008 , 2014 ; Sirota et al, 2015a ; see discussion of “ Chances ” below in Section Reasoning with Natural Frequencies). Recent re-analyses of data from Gigerenzer and Hoffrage ( 1995 ) show that problems focusing on individuals (compared to samples, or “numbers”) indeed lead to fewer Bayesian responses (Hafenbrädl and Hoffrage, 2015 ).…”
Section: The Bayesian Problem: From Words and Numbers To Meaningful Smentioning
confidence: 99%